1999
DOI: 10.1046/j.1440-1711.1999.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of recombinant viruses to deliver cytokines influencing the course of experimental bacterial infection

Abstract: SummaryThe feasibility of using viral constructs expressing cytokine genes to influence the course of bacterial infection was tested in mice. The mice were first infected with vaccinia or fowlpox viruses expressing the cytokine of interest, then challenged with the facultative intracellular bacterial pathogen Listeria monocytogenes. The course of infection was assessed by subsequent bacterial counts. Expression of IFN-γ or TNF was protective. Vaccinia virus was more efficient at delivering IFN-γ-mediated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…Thus, it can be said that the rEpiF1 fusion antigen generated a mixed immune response. This has an advantage for a vaccine candidate as it has been reported that the antigens that generated mixed immune response conferred better protection in comparison to those which induced only a Th2 response (Cheers et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be said that the rEpiF1 fusion antigen generated a mixed immune response. This has an advantage for a vaccine candidate as it has been reported that the antigens that generated mixed immune response conferred better protection in comparison to those which induced only a Th2 response (Cheers et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be the result of the observed combined reduction in antiviral effectors such as CD8 ϩ CTL precursor (CTLp) development, IFN-␥ expression, macrophage activation, and inducible nitric oxide production (4,41). While no reduction in splenic NK cell activity was observed in infected CBA mice (41), a significant reduction was found when SCID mice were infected with VACV expressing IL-4 (4).…”
Section: Discussionmentioning
confidence: 99%
“…TH2 cells are involved in humoral (antibody-mediated) immunity and produce IL-4, IL-5, and IL-10 (31, 34). IL-4 is also an important regulator of isotype switching and the stimulation of immunoglobulin E production in B lymphocytes (8-10).Different reports have provided contradictory evidence suggesting that IL-4 may have either protective or detrimental effects during viral infection (4,11,12,24,29,42). Recently, a recombinant mousepox virus expressing IL-4 was reported to have greatly increased pathogenicity in infected mice (22).…”
mentioning
confidence: 99%
“…Different reports have provided contradictory evidence suggesting that IL-4 may have either protective or detrimental effects during viral infection (4,11,12,24,29,42). Recently, a recombinant mousepox virus expressing IL-4 was reported to have greatly increased pathogenicity in infected mice (22).…”
mentioning
confidence: 99%